2020
DOI: 10.2298/abs190715061n
|View full text |Cite
|
Sign up to set email alerts
|

Endangered species’ trait responses to environmental variability in agricultural settings

Abstract: Understanding the spatial and temporal effects of variable environmental conditions on demographic characteristics is important in order to stop the decline of endangered-species populations. To capture interactions between a species and its environment, in this work the demographic traits of the European ground squirrel (EGS), Spermophilus citellus, were modeled as a function of agricultural landscape structure. The habitat suitability index was determined for 20 localities within the study area based on habi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…This relation indicates that the type of land use plays an important role for the ecological functions of the ecosystems, which is more marked in the Mediterranean climate [62]. Moreover, an increase in vegetation productivity most likely affects ground squirrels via changes in vegetation height and, consequently, foraging activity [63,64]. The combination of an arid Mediterranean climate and intense habitat management resulting in sparse vegetation (low NDVI) could influence the home range of individuals, which try to surpass the food limitations by foraging in larger areas in poor environments [14,65,66].…”
Section: Discussionmentioning
confidence: 99%
“…This relation indicates that the type of land use plays an important role for the ecological functions of the ecosystems, which is more marked in the Mediterranean climate [62]. Moreover, an increase in vegetation productivity most likely affects ground squirrels via changes in vegetation height and, consequently, foraging activity [63,64]. The combination of an arid Mediterranean climate and intense habitat management resulting in sparse vegetation (low NDVI) could influence the home range of individuals, which try to surpass the food limitations by foraging in larger areas in poor environments [14,65,66].…”
Section: Discussionmentioning
confidence: 99%
“…The latest assessment emphasizes land conversion and infrastructural development, along with the abandonment of traditional management practices, as the main drivers of its habitat fragmentation and consequent population decline. Based on the latest studies, these adverse conditions are also found in Serbia, and demand immediate conservation actions [15,[21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…The species' range in Vojvodina has shrunk by 70% compared to the available historical data, and about half of the populations presently reside outside the protected area network [23]. To halt and potentially reverse the local population decline caused by anthropological activities and environmental variability, adequate habitat management plans and programs need to be established [24]. Detailed studies regarding habitat conditions and feeding habits are an important structural component of local habitat management plans and programs.…”
Section: Introductionmentioning
confidence: 99%